The Idea of ​​Integral, Harmonious, and Universal Islamic Education According to M. Natsir - Umi Lathifah; Rustam Ibrahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education has been a fundamental pillar of human civilization since ancient times. Humans have learned to understand life, even up to the modern era we live in. With increasingly sophisticated and advanced technology, education plays a role as a tool for developing human potential. Humans are unique among other creatures. Experts study them from diverse perspectives. Quraish Shihab stated that many scientists have studied humans, but the results remain limited. What we do know is that humans are composed of several specific parts. This, too, depends on each individual's perception.